Exploring solvent dependent catecholase activity in transition metal complexes: an experimental and theoretical approach. (6th January 2020) - I., Mantasha; Shahid, M.; Kumar, Manjeet; Ansari, Azaj; Akhtar, Muhammad Nadeem; AlDamen, Murad A.; Song, You; Ahmad, Musheer; Khan, Ishaat M.
Abstract : Four coordination compounds are designed with pyridinemethanol ligands, characterized with spectral, magnetic and X-ray analyses, and assessed for catecholase activity in various solvents. Abstract : In contrast to polynuclear complex models for biomimetic activity, a series of mononuclear complexes are designed in this work in order to assess their catecholase activity and kinetics. Four new complexes, namely, [Mn(pdmH2 )(Phen)Cl]Cl·H2 O (1 ), [Mn(pmmH)2 (SCN)2 ] (2 ), [Ni(pmmH)2 (SCN)2 ] (3 ) and [Zn(phen)3 ][(pdm)]·11H2 O (4 ) utilizing an amino alcohol ligand, pyridine-2, 6-dimethanol (pdmH2 ) or 2-pyridinemonomethanol (pmmH), and an auxiliary ligand, 1, 10-phenanthroline (phen) or thiocyanate (SCN − ), are synthesized. The complexes are characterized by elemental analysis, FTIR, UV-visible, EPR, fluorescence (solution and solid state), Hirshfeld surface analysis, magnetic, single crystal X-ray and DFT/TD-DFT studies. X-ray structures confirm the geometry around the M(ii ) ions to be octahedral in all the complexes. In 1–3, the primary aminoalcohol ligand binds to a metal ion in a neutral (pdmH2 or pmmH) mode while 4 exists as a cation–anion type complex where a deprotonated ligand (pdm 2− ) is present in the outer sphere having no coordination to the metal. The Zn(ii ) complex also shows remarkable luminescence in the solid state photoluminescence spectrum. Variable temperature magnetic studies show the presence of antiferromagnetic exchange in 1–3 ( θ = −2.8, −1.7 and −5.2, respectively) with the observation of anisotropy ( D = 4.0 and E = 3.4) in 3 . DFT/TD-DFT results provide ample information regarding the structures, spin densities, charge distribution, and electronic spectra along with the transitions. The spin density values, ρ = 4.793, 4.792 and 1.676, confirm the presence of five, five and two unpaired electrons on the metal d-orbitals of 1, 2 and 3, respectively. Interestingly, solvent dependent catecholase activity has been observed for the first time in mononuclear Mn(ii ) complexes (1 and 2 ) with K cat = 2602.8 h −1 (acetonitrile), 1490.4 h −1 (methanol) for 1, and 1083.6 h −1 (acetonitrile), 806.4 h −1 (methanol) for 2 . This can be rationalized in terms of the coordinating powers of the solvent, i.e., DMSO > MeOH > MeCN. Further, the order of activity in 1 and 2 ( i.e., 1 > 2 ) and inactivity of 3 and 4 are very well corroborated by DFT which ascertains the highest charge contribution on the metal in 1 [33% on HOMO and 2% on LUMO of Mn(ii )] resulting in the formation of the most stable metal–substrate adduct, thus enhancing the activity.